FIBER CONCRETE STUDY WITH THE ADDITION OF PALM SIGNS ON THE COMPRESSIVE STRENGTH OF CONCRETE - Farizal, Teuku; Rahman, Aulia; Basrin, Defry; Febrianti, Dian; Murhaban, Murhaban (RADJA PUBLIKA, 2023)
Concrete is part of a construction formed by a mixture of cement, water, fine aggregate, coarse aggregate either crushed stone or gravel and other mixed materials. Fiber concrete is concrete whose method of manufacture is added with fiber, both man-made fiber and natural fiber such as palm fruit bunches. The addition of palm fruit bunches to the concrete mix is ​​expected to increase the compressive strength of concrete. The percentage of addition of palm marks is 6%, 8% and 11% by weight of cement with FAS 0.35. The test object used was a cube (15 x 15 x 15) cm with a total of 12 test objects for 7 days of age and 12 test objects for 28 days of age. The results of the 7-day average compressive strength test for BTTS were 310.76 kg/cm2, BDTS (6%) were 260.23 kg/cm2, BDTS (8%) were 237.83 kg/cm2 and BDTS (11%) were 244.67 kg/cm2. cm2. Testing the compressive strength at an average age of 28 days obtained results for BTTS of 342.20 kg/cm2, BDTS (6%) of 294/18 kg/cm2, BDTS (8%) of 269.42 kg/cm2 and BDTS (11%) of 279.72 kg/cm2. From the results of the compressive strength test, the average test age of 7 days and 28 days shows that the addition of palm fiber can reduce the compressive strength of concrete in all variations, namely 6%, 8% and 11%.